Manejo integrado de Alurnus humeralis en el cultivo de palma aceitera (Elaeis guineensis ) en el Ecuador - LIMONES JIMENEZ, VICTOR DANIEL (2023)
In this bibliographic research, information on the appearance and etiology of the insect was also compiled; Also of the chemical and biological controls used to combat this plague. Oil palms are a crop of great importance in Ecuador since it has a planted area of 270,000 ha, and 87,13% of palm growers are entrepreneurs who own land of less than 50 ha, it also provides work for 137,000 people on a regular basis. direct and indirect, which shows the economic and social scale that cultivation has in Ecuador. Integrated pest management in oil palm cultivation allows protecting pest damage below the economically tolerable level. Integrated Pest Management is a mixture of various control measures that subject the risk to human health and property in the environment from agricultural exploitation. Alurnus humeralis, is a phytophagous insect that causes damage to oil palm plants both in its larval and adult stages; assuming a life cycle of 428 days with an average of 239 days in the larval stage and 113 days in the adult.